Effect of hyperandrogenism in obese PCOS patients: GLP-1 receptor agonists plus metformin versus metformin monotherapy–a systematic review and meta-analysis (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in reproductive-aged women, characterized by hyperandrogenism, ovulatory dysfunction, and metabolic disturbances, particularly in overweight and obese individuals. Insulin resistance and excess adiposity worsen androgen excess, emphasizing the need for therapies targeting both metabolic and hormonal imbalance. Objective: To evaluate the effectiveness of GLP-1RA plus metformin compared to metformin alone in reducing hyperandrogenism, measured by sex hormone-binding globulin (SHBG) and free androgen index (FAI), in overweight and obese women with PCOS. Methods: A systematic review and meta-analysis were conducted following PRISMA guidelines. Literature searches were performed in PubMed, Cochrane Library, and ScienceDirect (January 2000–June 2025). Eligible studies included randomized and clinical trials comparing GLP-1RA plus metformin versus metformin alone in overweight/obese women with PCOS, reporting SHBG and/or FAI outcomes. Data extraction, risk of bias assessment (RoB-2), and quantitative synthesis were conducted. Five studies with 252 participants were included. Results: Combination therapy significantly increased SHBG (MD = 7.82; 95% CI: 4.98–10.66; p < 0.00001; I² = 31%) and reduced FAI (MD = −3.16; 95% CI: −4.09 to −2.23; p < 0.00001; I² = 0%) compared to metformin alone. Conclusion: GLP-1RA combined with metformin is more effective than metformin monotherapy in improving hyperandrogenism in overweight and obese women with PCOS.